Analisis Faktor-Faktor Yang Mempengaruhi Minat Transaksi Pada Penggunaan Teknologi E-Wallet - Natasha Natasha; Filani Zikri Hassan; Rini Syarif (Jurnal Informatika Kesatuan, 2022)
This study aims to analyze the factors that influence the interest of transactions on the use of e-wallet. In this study, the independent variable (X) is the perception of benefits, quality, ease of use, and trust and the dependent variable (Y) is the attitude of use. The population taken in this study are active and passive users of the Fintech OVO application. The sampling method taken is non probability sampling with the results of 100 respondents used as samples. While the object of this research is OVO users who have used the OVO electronic wallet several times. The source of the data obtained in this study were the responses of respondents obtained from the results of the questionnaire about the effect of perceived benefits, quality, ease of use, and the confidence distributed to the sample. Scoring by agree-disagree scale technique by developing statements that produce answers to agree-disagree in various ranges of values. The order of scale consists of the numbers 1 (Strongly Disagree) to 5 (Strongly Agree) for all variables. The results of this study indicate that the variables that influence the interests of E-Wallet OVO transactions are the benefits of E-Wallet OVO, the quality of E-Wallet OVO, ease of use of E-Wallet OVO and trust in E-Wallet OVO. Keywords: E-Wallet, transaction interest, fintech, OVO